PELAGIC FISHERIES OF VIZHINJAM - Radhakrishnan, N (Indian Journal of Fisheries, 2011)
The average annual marine fish production at Vizliinjam has been estimated tobe about 2600 tonnes of which the pelagic fishes constitute 69%. The fishery, seasonalfluctuations and biological details of the different species of Sardinella, Dussumieria,Anchoviella and Caranx are presented. Brief descriptions on the fishery of ribbon fish,scombroids and other pelagic species are also given.